Maternal hsa-miR-423-5p associated with the cognitive development of babies in pregnant women without mental disorders - do Amaral, Cainá Corrêa; Nedel, Fernanda; Ferrúa, Camila Perelló; Garcia, Tiago Fernandez; Corrêa, Geovanna Peter; Giorgi, Roberta; Longoni dos Santos, Aline; de Assis, Adriano Martimbianco; de Avila Quevedo, Luciana; Ghisleni, Gabriele Cordenonzi; de Matos, Mariana Bonati; Pinheiro, Karen Amaral Tavares; et al. (Frontiers in Human Neuroscience, 2024)
Background: MicroRNAs (miRNAs) are small non-coding RNAs capable of regulating gene expression post-transcriptionally. MiRNAs are recognized as key regulators of diverse biological and developmental processes. During the pregnancy-puerperal cycle, numerous changes occur in the female body for the formation, growth, and development of the baby. After birth, there is a critical period in child development, as rapid gains in the physical, cognitive, and socio-emotional domains constitute the "building blocks" of children's later growth. Objective: was to investigate the association between maternal expression of has-miR-423-5p during the first and second trimester of pregnancy and neurocognitive development at 90 days of life in infants. Methods: This is a longitudinal study included in a population-based cohort study, carried out in a city in southern Brazil. The Bayley III was used to assess the outcome of the babies' cognitive development. Blood samples from mothers were obtained for RNA extraction from serum and analysis of miRNA expression by qRT-PCR. Results: 87 dyads (mother-baby) were included. The average gestational age was 15.86 weeks (SD±5.55). An association of maternal miRNA with infant cognitive development was found, as maternal miR-423-5p increases, infants' cognitive development increases by 2.40 (95% CI 0.37; 4.43, p = 0.021) points at three months of age. Conclusion: In this contextsense, it is possible suggested that to aim to use this miRNA as a biomarker of child neurocognitive development detectable in the prenatal period, thus allowing the planning of early interventions.